Produk Roti dalam Pola Konsumsi Pangan dan Keberadaan Label Halal dalam Keputusan Konsumsi Masyarakat (Kasus: Kota Bogor) - Silmy Kania Rizka; Yeti Lis Purnamadewi; Neneng Hasanah (AL-MUZARA'AH, 2018)
The pattern of bread consumption has increased significantly compared to the increase in the average in rice consumption. However, the increase in bread consumption was not balanced by the increase in the producers’ awareness to have halal certificate. Meanwhile, halal certified products are  only about 11.6% of the total existing products in Indonesia. For this reason, this study aims to analyze the consumption pattern of bread products, consumer’s perceptions of the halal labels and their influence on the decision to purchase halal-labeled bread products , and factors that influence the decision. The method used in this research are logistic regression and qualitative descriptive. The results of the analysis shows that bread products are the second source of carbohydrates after rice and the higher the income class have a higher level of bread product consumption. Based on the consumer’s perception, the existence of the halal label in packaging of bread products is a main consideration in the decision of purchasing bread products for most of households consumers, but the perception and a fact of the purchasing have not been consistent. The results of the logistic regression analysis shows that the variable of halal awareness, duration of education, dummy of origin area, and dummy of lower income class significantly affect the decision of bread products consumption.